Prototype Design and Analysis of Wireless Vibration Sensor - Akhondi, Mohammad Reza; Talevski, Alex; Chou, T. (Conference Publishing Services, 2010)
Since the technology era began, sensor systems have been frequently updated. In order to keep the sensor up to date, components are designed using a modular approach that can be updated with the latest technology. The objective of this paper is to illustrate the design of a vibration sensor that integrates an enhanced Mechanism for Hardware Health Monitoring (MHHM). The design achieves the digitizing, wireless communication and modularity aspects of this system as required. The selection of appropriate components is also presented in the paper as a guide.